Novel use of balloon tamponade saves a patient with uterine inversion in severe shock - Yadav, Sumitra; Malhotra, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A patient with G1P0 status 38 weeks pregnancy with pain with no high risk delivered at PHC, Hatod, Madhya Pradesh (India). She delivered a male baby by spontaneous vaginal delivery of 3.1 kg. All of sudden after 2nd stage of labour, her 3rd stage of labour was eventful. Placenta did not come out spontaneously so controlled cord traction was given by the ANM over the PHC. She was given intramuscular oxytocin 5 IU. She did the traction with proper care but inspite of that while doing so placenta got separated but there was complete uterine inversion. ANM herself tried to reposit the uterus but could not do so. So ANM immediately referred her from PHC to MYH, Indore, Madhya Pradesh (India).